(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Introduction: Pregnancy can present with multiple skin manifestations. It can be either physiological, pre-existing skin disease or development of new dermatoses. Few specific dermatoses like intrahepatic cholestasis of pregnancy and pemphigoid gestationis are associated with increased risk of prematurity, Intrapartum fetal distress, preterm delivery and still births. So, ante partum surveillance is recommended for patients with these diseases as they carry fetal risk. Objective: To study the spectrum and frequency of specific dermatoses of pregnancy and to see fetal outcome in mother associated with these dermatoses. Methods: A hospital based observational study was conducted in the Department of obstetrics and gynaecology along with collaboration of department of dermatology at Bashundhara Addin Medical College Hospital for a period of January 2020 to December 2022.A total 51 pregnant women were included in the study after taking informed consent. Detailed history including demographics and symptoms relating to skin disorder, site of skin lesion, onset in relation to gestational age of pregnancy, past or family history of similar lesions associated with medical disorder, were filled in self-administered questionnaires and physical examination was carried out by a dermatologist. Results: The maximum age group of this study was 20-29 years (66.66%). More were in middle socioeconomic class group 34(66.66%). Thirty-five (68.63%) patient develops specific dermatoses of pregnancy in 3rd trimester of pregnancy. Prurigo of pregnancy was most common skin lesion 30(58.82%) in study. Prematurity and intrauterine fetal growth restriction were found in 7 patients. Two patients developed intrauterine fetal death in this study. Conclusion: Pregnant women are prone to suffer from a wide range of dermatological problems. These pruritic dermatoses are unique to the gravid state. A detailed history and awareness of clinical presentation, confirmation of the diagnosis and the most appropriate laboratory evaluation should be done in an effort to minimize maternal and fetal morbidity. Bangladesh J Obstet Gynaecol, 2024; Vol. 39(1): 12-17